Iron‐Catalyzed Allylic C(sp3)−H Silylation: Spin‐Crossover‐Efficiency‐Determined Chemoselectivity - He, Peng; Guan, Mu‐Han; Hu, Meng‐Yang; Zhou, Yuan‐Jun; Huang, Ming‐Yao; Zhu, Shou‐Fei (Angewandte Chemie International Edition, 2024)
The nuanced role of spin effects remains a critical gap in designing proficient open‐shell catalysts. This study elucidates an iron‐catalyzed allylic C(sp3)−H silylation/alkyne hydrosilylation reaction, in which the spin state of the open‐shell iron catalyst dictates the reaction kinetics and pathway. Specifically, spin crossover led to alkyne hydrosilylation, whereas spin conservation resulted in a novel allylic C(sp3)−H silylation reaction. This chemoselectivity, governed by the spin‐crossover efficiency, reveals an unexpected dimension in spin effects and a first in the realm of transition‐metal‐catalyzed in situ silylation of allylic C(sp3)−H bonds, which had been previously inhibited by the heightened reactivity of alkenes in hydrosilylation reactions. Furthermore, this spin crossover can either accelerate or hinder the reaction at different stages within a single catalytic reaction, a phenomenon scarcely documented. Moreover, we identify a substrate‐assisted C−H activation mechanism, a departure from known ligand‐assisted processes, offering a fresh perspective on C−H activation strategies. An iron‐catalyzed allylic C(sp3)−H silylation/alkyne hydrosilylation reaction was developed in which the spin state of the open‐shell iron catalyst dictates the reaction kinetics and pathway. This chemoselectivity, governed by the spin‐crossover efficiency, indicates an unexpected dimension in spin effects.